Suppressor Mutations in Type II Secretion Mutants of Vibrio cholerae: Inactivation of the VesC Protease - Chelsea S. Rule (American Society for Microbiology, 2020)
ABSTRACT The type II secretion system (T2SS) is a conserved transport pathway responsible for the secretion of a range of virulence factors by many pathogens, including Vibrio cholerae. Disruption of the T2SS genes in V. cholerae results in loss of secretion, changes in cell envelope function, and growth defects. While T2SS mutants are viable, high-throughput genomic analyses have listed these genes among essential genes. To investigate whether secondary mutations arise as a consequence of T2SS inactivation, we sequenced the genomes of six V. cholerae T2SS mutants with deletions or insertions in either the epsG, epsL, or epsM genes and identified secondary mutations in all mutants. Two of the six T2SS mutants contain distinct mutations in the gene encoding the T2SS-secreted protease VesC. Other mutations were found in genes coding for V. cholerae cell envelope proteins. Subsequent sequence analysis of the vesC gene in 92 additional T2SS mutant isolates identified another 19 unique mutations including insertions or deletions, sequence duplications, and single-nucleotide changes resulting in amino acid substitutions in the VesC protein. Analysis of VesC variants and the X-ray crystallographic structure of wild-type VesC suggested that all mutations lead to loss of VesC production and/or function. One possible mechanism by which V. cholerae T2SS mutagenesis can be tolerated is through selection of vesC-inactivating mutations, which may, in part, suppress cell envelope damage, establishing permissive conditions for the disruption of the T2SS. Other mutations may have been acquired in genes encoding essential cell envelope proteins to prevent proteolysis by VesC. IMPORTANCE Genome-wide transposon mutagenesis has identified the genes encoding the T2SS in Vibrio cholerae as essential for viability, but the reason for this is unclear. Mutants with deletions or insertions in these genes can be isolated, suggesting that they have acquired secondary mutations that suppress their growth defect. Through whole-genome sequencing and phenotypic analysis of T2SS mutants, we show that one means by which the growth defect can be suppressed is through mutations in the gene encoding the T2SS substrate VesC. VesC homologues are present in other Vibrio species and close relatives, and this may be why inactivation of the T2SS in species such as Vibrio vulnificus, Vibrio sp. strain 60, and Aeromonas hydrophila also results in a pleiotropic effect on their outer membrane assembly and integrity.